PENGEMBANGAN TRANSVERSAL SKILLS PESERTA DIDIK DALAM PEMBELAJARAN PENDIDIKAN AGAMA ISLAM : PENGEMBANGAN TRANSVERSAL SKILLS PESERTA DIDIK DALAM PEMBELAJARAN PENDIDIKAN AGAMA ISLAM - Agustina Tarik, Atika; Rahmania Azis, Annisa; Asrohah, Hanun (UNIVERSITAS MUHAMMADIYAH SURABAYA, 2025)
The era of the Fourth Industrial Revolution has brought significant changes in various aspects of life, including education. Islamic Religious Education (PAI) plays an important role in developing the transversal skills needed by students to face challenges in the modern world. This research aims to explore how PAI can contribute to the development of skills such as adaptability, collaboration, problem-solving, creativity, and effective communication. Through a literature study approach, this research analyzes various relevant scientific references, including academic journals and articles discussing the integration of religious values with 21st-century skills. The results of the study indicate that PAI not only serves as a means of teaching religious values but also as a tool to equip students with applicable skills in everyday life. Thus, PAI has the potential to shape a generation that is morally upright and ready to compete in an increasingly complex digital era.